2014
DOI: 10.1051/0004-6361/201323264
|View full text |Cite
|
Sign up to set email alerts
|

VLTI/AMBER observations of cold giant stars: atmospheric structures and fundamental parameters

Abstract: Aims. The main goal of this research is to determine the angular size and the atmospheric structures of cool giant stars ( Oct, β Peg, NU Pav, ψ Peg, and γ Hya) and to compare them with hydrostatic stellar model atmospheres, to estimate the fundamental parameters, and to obtain a better understanding of the circumstellar environment. Methods. We conducted spectro-interferometric observations of Oct, β Peg, NU Pav, and ψ Peg in the near-infrared K band (2.13−2.47 μm), and γ Hya (1.9−2.47 μm) with the VLTI/AMBER… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…We also observe a monotonic decrease beyond 2.3 μm, which may be caused by pseudocontinuum contributions from CO or by contributions from water vapor. We observed the same phenomenon previously for the RSGs VY CMa (Wittkowski et al 2012), AH Sco, UY Sct, and KW Sgr (Arroyo-Torres et al (2013), as well as for the smallamplitude pulsating red giants RS Cap (Marti-Vidal et al 2011), BK Vir (Ohnaka et al 2012), α Tau (Ohnaka 2013), and β Peg (Arroyo-Torres et al 2014).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…We also observe a monotonic decrease beyond 2.3 μm, which may be caused by pseudocontinuum contributions from CO or by contributions from water vapor. We observed the same phenomenon previously for the RSGs VY CMa (Wittkowski et al 2012), AH Sco, UY Sct, and KW Sgr (Arroyo-Torres et al (2013), as well as for the smallamplitude pulsating red giants RS Cap (Marti-Vidal et al 2011), BK Vir (Ohnaka et al 2012), α Tau (Ohnaka 2013), and β Peg (Arroyo-Torres et al 2014).…”
Section: Resultssupporting
confidence: 88%
“…In particular we calculated the effective temperature, the luminosity, the Rosseland-mean radius, the bolometric flux, and the distance in the same way as described in detail by Arroyo-Torres et al (2014). We used the BVJHKs magnitudes from Kharchenko (2001) and Cutri et al (2003) and the IRAS flux from IRAS (1988).…”
Section: Fundamental Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainties are of the order of 50 K. Mérand et al (2010) showed that for a K0III star, the uncertainty in the diameter due to different models do not exceed 0.5% (and is thus negligible for the determination of T eff ). It may be worse for M stars but the uncertainty should not exceed ∼100 K. We note that, recently, Arroyo-Torres et al (2014) derived an effective temperature of T eff = 3909 ± 187 K for our coolest star β Peg based on VLTI/AMBER diameters, more than 450 K warmer than the temperature of Mozurkewich et al (2003). Dehaes et al (2011) derived T eff = 3600 ± 300 K from modelling the spectral energy distributions (SED), for the same star.…”
Section: Stellar Parametersmentioning
confidence: 71%